SUBSTITUTION OF AMMONIUM SULFATE FERTILIZER ON UPLAND SUGARCANE CULTIVATION AND ITS EFFECTS ON PLANT GROWTH, NUTRIENT CONTENT AND SOIL CHEMICAL PROPERTIES - Nurhidayati, Nurhidayati; Basit, Abdul; Sunawan, Sunawan (AGRIVITA, Journal of Agricultural Science, 2013)
The aim of this research was to compare the effect of substitution of Ammonium Sulfate (AS) fertilizer on sugarcane growth, nutrient content, and soil chemical properties. This research was conducted on up-land of sugarcane plantation in Tegalweru village, Dau district, Malang regency. This study tested ten treatments consisting of three treatments using AS fertilizer, six treatments using AS substitute fertilizers that used combination of Urea, Gypsum, and bio-compost and one control (no fertilizer). This research used randomized complete block design with three replications. The results showed that the plant growth between the treatment used AS fertilizer and AS substitute was not significantly different. However, the treatment used 400 kg Urea per ha+938 kg Gypsum per ha tended to have the best plant growth and the highest N uptake. For the treatments using AS substitute fertilizer, the higher the application rate was, the higher the soil N and S contents were. The treatments used AS fertilizer due to lower soil pH than AS substitute fertilizer. Based on this research, it can be concluded that the use of alternative fertilizers as a substitute of the AS fertilizer is recommended to reduce an adverse impact on soil fertility. Keywords: AS fertilizer, AS substitute fertilizer, sugarcane, nutrient content, soil chemical properties